Iringan Musik dalam Tilawah Qur’an: Perspektif Tafsir - Fariz Abdillah; Septiawadi Kari Mukmin; Beko Hendro (Studia Quranika, 2026)
This study explores the phenomenon of musical accompaniment in the recitation of the Qur’an (Tilawah Qur’an) from the perspective of classical and contemporary Islamic scholarship. As a sacred practice, Qur’anic recitation requires reverence and concentration, yet the use of music alongside tilawah has sparked significant debate. Some scholars argue that music enhances the aesthetic and emotional aspects of recitation, while others reject it for potentially undermining its sanctity. Employing a qualitative method with a literature review approach, this research refers to Sayyid Qutb’s Fi Zhilalil Qur’an, Fakhruddin al-Razi’s Tafsir al-Kabir, as well as the views of Al-Ghazali, Ibn Taymiyyah, and Yusuf al-Qaradawi. The findings reveal that the Qur’an neither explicitly permits nor prohibits music, but rather emphasizes tartil (measured recitation), khushu’ (reverence), and respect for its sacredness. Sayyid Qutb strongly opposed the use of music, considering the Qur’an’s beauty sufficient without external additions, while Fakhruddin al-Razi regarded music as neutral and permissible so long as it does not cause distraction. In conclusion, musical accompaniment in Tilawah Qur’an is an ijtihadi issue that requires careful consideration, taking into account context, intention, and its impact on spiritual focus and the comprehension of Qur’anic meaning.